Performance of a hybrid capture-based target enrichment next-generation sequencing for the identification of respiratory pathogens and resistance-associated genes in patients with severe pneumonia - Wei-Yu Hsu; Ting-Wei Kao; Hsin-Ching Cho; Sheng-Yuan Ruan; Tai-Fen Lee; Yu-Tsung Huang; Jung-Yien Chien (Microbiology Spectrum)
ABSTRACT Severe pneumonia remains the leading infectious cause of death worldwide. The time-consuming nature and suboptimal sensitivity of sputum cultures hamper prompt pathogen detection for tailored treatments. Advanced techniques such as polymerase chain reaction (PCR) and next-generation sequencing (NGS) offer rapid genetic pathogen detection and identification of antimicrobial resistance (AMR) genes. However, the performance of hybrid capture-based target enrichment NGS, e.g., Respiratory Pathogen ID/AMR Enrichment Panel (RPIP), for pathogen detection in patients with severe pneumonia remains uncertain. A prospective study involving adults with severe pneumonia was conducted. Respiratory samples from the lower respiratory tract were collected via bronchoalveolar lavage, bronchial washing, or endotracheal tube suction. The performance of RPIP in pathogen and AMR-associated gene detection was compared to that of conventional culture methods and the multiplex PCR-based FilmArray Pneumonia Panel (FilmArray-PN). A total of 83 subjects were enrolled. The most prevalent pathogens detected by RPIP were Rothia mucilaginosa, Stenotrophomonas maltophilia, Pseudomonas aeruginosa; herpes simplex virus-1, cytomegalovirus, and Epstein-Barr virus, and Pneumocystis jirovecii. Overall, the positive and negative agreement rates for bacterial detection were 63.6% and 97.5% between RPIP and culture methods, respectively, and 55.8% and 99.4% between FilmArray-PN and culture methods, respectively. Compared to FilmArray-PN, RPIP exhibited significantly better detection rates for bacteria (P = 0.029), viruses (P < 0.001), and fungi (P < 0.001) and identified additional blaOXA, blaCMY as extended-spectrum β-lactamase genes and blaOXA, blaSHV as carbapenemase genes. In conclusion, RPIP can sensitively profile respiratory pathogens and is a promising tool for detecting multiple microorganisms and AMR-associated genes in patients with severe pneumonia.IMPORTANCESensitive pathogen detection is pivotal for timely treatment by tailoring adequate antimicrobial agents. Unlike conventional phenotypic approach, novel measures using molecular interrogation appear promising. This study aimed to elucidate the efficacy of a hybrid capture-based target enrichment next-generation sequencing technique (Respiratory Pathogen ID/AMR Enrichment Panel, RPIP) as exemplified in a cohort with severe pneumonia. Pathogen landscape in the population was illustrated by these three methodologies. As compared with multiplex polymerase chain reaction-based FilmArray Pneumonia Panel and conventional culture, RPIP demonstrated significantly improved sensitivity in identifying bacteria, viruses, and fungi. The RPIP also exhibited better performance in identifying different pathogens in patients co-infected with multiple microorganisms. Additionally, the genotypes contributing to antimicrobial resistance were determined by RPIP. The study facilitated the implementation of molecular diagnosis by presenting real-world data, whereas future studies are mandated to generalize such an approach toward different clinical settings.